Analisis faktor akuntansi dan non akuntansi yang mempengaruhi prediksi peringkat obligasi pada perusahaaan non keuangan yang terdaftar di BEI dan diperingkat oleh PEFINDO periode 2009-2013 - A, Al-azhar; Ma’arij, Arinurtry; ', Zulbahridar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of accounting and non-accounting factors on bond ratings in all non-financial companies listed in the Indonesia Stock Exchange and registered in bond ratings issued by PT. PEFINDO period from 2009 to 2013. The sample used in this study amounted to 130 bonds from 41 non-financial companies. The sampling technique was determined by the method of targeted Sampling (purposive sampling), while the method of analysis used logistic regression analysis. The results of this study indicate that the variable growth, size, liquidity, and sinking fund have positive effect on bond ratings. While solvency, profitability, leverage, secure, maturity, and auditor reputation have no significant effect on bond ratings.Keywords : Bond Rating, Growth, Size, Liquidity, Solvency, Profitability, Leverage, Secure, Maturity, Sinking fund, Auditor Reputation